Effectiveness of the Free Trade Zone Policy as a Solution to Improve the Economy in Batam - Agustianto, Agustianto; Sudirman, Lu; Setiawan, Marthalia (Al-Adalah: Jurnal Hukum dan Politik Islam, 2024)
This research aims to explore and analyze the regulations and implementation of the Free Trade Zone (FTZ) policy in the context of improving the economy in Batam City, Indonesia. This research uses non-doctrinal or empirical research. The applied problem approach involves three main approaches: a statutory approach, a conceptual approach, and a sociological or empirical approach. The data analysis technique used is qualitative analysis with a deductive data presentation pattern. Researchers will explore the regulations related to FTZs in Batam City and analyze the economic implications of these policies. Research findings show that in 2022 after the publication of PP No. 41 of 2021 has had an impact on improving the economy in Batam, including increasing export and import transactions so that Batam City's trade balance recorded a surplus of USD 2,262.24 million. Increase in the number of industrial and investment areas.Â It is hoped that the analysis of these findings will provide better insight into the contribution of FTZ policies to economic development at the local level